Association and dissociation of the GlnK–AmtB complex in response to cellular nitrogen status can occur in the absence of GlnK post-translational modification - Radchenko, Martha V.; Thornton, Jeremy; Merrick, Mike (Frontiers in Microbiology, 2014)
PII proteins are pivotal players in the control of nitrogen metabolism in bacteria and archaea, and are also found in the plastids of plants. PII proteins control the activities of a diverse range of enzymes, transcription factors and membrane transport proteins, and their regulatory effect is achieved by direct interaction with their target. Many, but by no means all, PII proteins are subject to post-translational modification of a residue within the T-loop of the protein. The protein’s modification state is influenced by the cellular nitrogen status and in the past this has been considered to regulate PII activity by controlling interaction with target proteins. However the fundamental ability of PII proteins to respond to the cellular nitrogen status has been shown to be dependent on binding of key effector molecules, ATP, ADP and 2-oxoglutarate which brings into question the precise role of post-translational modification. In this study we have used the Escherichia coli PII protein GlnK to examine the influence of post-translational modification (uridylylation) on the interaction between GlnK and its cognate target the ammonia channel protein AmtB. We have compared the interaction with AmtB of wild-type GlnK and a variant protein, GlnKTyr51Ala, that cannot be uridylylated. This analysis was carried out both in vivo and in vitro and showed that association and dissociation of the GlnK-AmtB complex is not dependent on the uridylylation state of GlnK. However our in vivo studies show that post-translational modification of GlnK does influence the dynamics of its interaction with AmtB.